STIMULATING ENTREPRENEURSHIP IN THE ROMANIAN EDUCATION SYSTEM - DORINA NIȚĂ (Annals of the University of Petrosani: Economics)
Romania is on its way to find and apply the most effective solutions in order to ensure a sustainable economic growth and stable and well paid employment. It is in fact a requirement often set out at European Union level which resulted in a series of strategies and programs among which one can highlight the support of entrepreneurship. One of the areas of intervention in this direction is represented by the adaptation of education systems to the new challenges by introducing elements of entrepreneurial culture in the curriculum of the European States, including Romania, the concept of “training firm” or initiatives through which students can accumulate work experience before completing University studies. The development of entrepreneurship among younger generations suppresses the fear of becoming unemployed and gives them the opportunity not only to start up their own business, but also to obtain benefits that exceed their wages. At the local/ regional/ national economy it is similar with a diversification of economic activities, increase employment, income and growing living standards.